NK-1 antagonist CP99994 inhibits stress-induced mast cell degranulation in rats - AKICI, AHMET; ERCAN, FERİHA (WILEY, 2004)
Mast cells are implicated in stress-induced inflammatory skin diseases such as psoriasis. Mechanisms of stress-induced mast cell degranulation however, are not entirely clear. Here we explore the role of activation of a Substance P (SP) receptor (NK-1) on mast cell degranulation upon exposure to stress in rats. A specific nonpeptide NK-1 antagonist, CP99994 was used to treat the rats either peripherally or intracerebroventricularly. Because increased SP activity in the brain may mediate the stress response, we also examined cutaneous mast cell degranulation after central injection of SP. Stress, as well as SP injected centrally, increased mast cell degranulation. Both central and peripheral injection of CP99994 prevented stress-induced mast cell degranulation. Surprisingly, the combination of stress with SP decreased mast cell degranulation, suggesting that high levels of SP may counteract the stress responses. Results in this animal model suggest that NK-1 antagonists may be used therapeutically to treat stress-induced inflammatory skin diseases; however, drug doses should be chosen carefully.
Keywords: CORTICOTROPIN-RELEASING HORMONE; INDUCED HISTAMINE-RELEASE; ENDOGENOUS SUBSTANCE-P; RECEPTORS; NK1